ЗМІСТОВИЙ АСПЕКТ КОНТРОЛЮ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ ВНЗ (Педагогіка вищої та середньої школи, 2008)
The semantic aspect of control of educational activity of students of higher educational establishments is examined in the article.